High spatial resolution imaging of light localization in hyperuniform disordered patterns of circular air pores in a dielectric slab - Granchi, Nicoletta; Spalding, Richard; Stokkereit, Kris; Lodde, Matteo; Petruzzella, Maurangelo; Otten, Frank V.; Sapienza, Riccardo; Fiore, Andrea; Florescu, Marian; Intonti, Francesca (Frontiers in Photonics, 2023)
Positioned in-between random structures and perfectly ordered photonic crystals, there is a special class of disordered photonic heterostructures, called hyperuniform disordered photonic structures. These materials, due to the presence of a photonic bandgap, combine the advantages of both disordered systems and ordered systems, since they have been shown to support in a small spatial footprint a high density of Anderson-localized modes which naturally occur at the bandgap edges with peculiar features like relatively high Q/V ratios. Different localization behaviors have been recently reported in hyperuniform disordered luminescent materials, with a well-established and widely studied design, based on disordered networks. Here, we explore an alternative design, based on circular holes of different sizes hyperuniformely distributed, that we investigate theoretically and experimentally by means of scanning near-field optical microscopy. We report that the spectral features of hyperuniform disordered networks can be extended also to a different design, that in turn displays pseudo-photonic bandgaps and light localization. The ability of generating different kinds of hyperuniform disordered photonic systems that share the same theoretical and experimental optical features can largely extend practical potentialities and integration in many optoelectronic applications.